Characteristics and management of oro-maxillofacial trauma in the emergency room during the COVID-19 pandemic: a retrospective cross-sectional Study - Yudianto, Cahyono; Sjamsudin, Endang; Sylvyana, Melita; Riawan, Lucky (Universitas Padjadjaran, 2023)
AbstractIntroduction: Oro-maxillofacial traumas comprise injuries to the face, jaws, or both; they include injury to any of the bony structures, skin, and soft tissues around the face. During the COVID-19 pandemic, human activity was mostly at home, with movement restrictions. The purpose of this study is to find out the types of characteristics and management of oro-maxillofacial traumas during the COVID-19 pandemic at the emergency room. Methods: A cross-sectional study was conducted to evaluate every maxillofacial trauma in patients treated by the oral surgeon in the emergency room at RSUP Dr. Hasan Sadikin Bandung Hospital. Incidence records were taken directly from case reports from January 2020 to December 2021. The variables considered were patient age, gender, etiologies, sites, classifications, and management of the trauma. Then integrated into a table to be analyzed epidemiologically. Results: There were 177 maxillofacial trauma patients registered in the Department of Oral and Maxillofacial Surgery. It was found that the gender ratio, female to male, is equal to 2.3:7.6. The 18-36 age group accounted for the largest subgroup in both sexes. Motorcycle accidents accounted for as much as 80.22% of the etiology of the most common traumas. While dentoalveolar (28.22%) was the most common site of the fracture, followed by the mandible (23.31%). Injuries around the mouth made up the largest portion (62.15%) of the areas that were directly impacted by the injuries, followed by injuries to the face (18.64%) and injuries to the mouth and nose (6.21%). Among the 177 patients mentioned above, 10.17% were hospitalized. Conclusion: Male’s are more likely to be involved in traffic accidents, mainly motorcycle crashes, which are the primary cause of traumas. Dentoalveolar fractures were the most common type of fracture, and the management of the oro-maxillofacial trauma is done according to the standard procedure.